Current status of stem cell treatments and innovative approaches for stress urinary incontinence - Seval, Mehmet Murat; Koyuncu, Kazibe (Frontiers in Medicine, 2022)
Stem cells are capable of self-renewal, differentiation, and the promotion of the release of chemokines and progenitor cells essential for tissue regeneration. Stem cell therapy has the potential to cure stress urinary incontinence according to preclinical models. In contrast, stem cell treatment has not been licensed for routine clinical usage. This article reviews the current state of stem cells for stress urinary incontinence research and recommends future avenues to facilitate practical uses of this potential therapy modality.